Building-integrated solar thermal systems based on vacuum-tube technology: Critical factors focusing on life-cycle environmental profile. (November 2016) - Lamnatou, Chr.; Cristofari, C.; Chemisana, D.; Canaletti, J.L.
Abstract: The present study refers to Building-Integrated Solar Thermal (BIST) systems based on vacuum-tube collectors and it consists of two parts. In the first part, a literature review is presented, including studies about vacuum-tube technology (vacuum-tube/BIST systems, the environmental profile of vacuum-tube collectors, etc.). Critical issues, for example related to the integration of vacuum-tube collectors into the building, are highlighted. The review shows that most of the proposed vacuum-tube/BIST concepts are about façade-integration and there are few studies about the environmental profile of vacuum-tube collectors. As a continuity of the issues presented in the first part, the second part includes a case study about the environmental comparison of a vacuum-tube/BIST system with a flat-plate/BIST configuration, based on life cycle assessment. The systems are gutter-integrated, patented and they have been developed/tested at the University of Corsica, in France. Multiple life-cycle impact assessment methodologies, environmental indicators, scenarios and databases are adopted. The results reveal that the energy-payback time is 1.8 and 0.5 years, for the flat-plate/BIST and for the vacuum-tube/BIST, respectively, while by using recycling these values become 0.5 and 0.1 years, respectively. Energy-return-on-investment, greenhouse-gas payback time and avoided impact during use phase (by adopting USEtox, ecological footprint and France´s electricity as well as with reference domestic-gas-boiler CO2.eq emissions) are also presented. The findings of the present work: 1) are compared with the literature and good agreement is observed, 2) verify that considerably higher impact can be avoided by utilizing the vacuum-tube/BIST instead of the flat-plate/BIST system.